ANALISIS KELAYAKAN USAHATANI KAKAO DAN MOTIVASI PETANI DALAM BUDIDAYA KAKAO (Studi Kasus di Desa Putat, Kecamatan Patuk, Kabupaten Gunungkidul) - Pantja Siwi V R Ingesti; Hartini; M.Farhan Riza Dalimunthe (Jurnal Pertanian Agros, 2026)
This study aims to analyze the feasibility level of the farming business and the level of farmer motivation in cultivating cocoa plants. A quantitative descriptive method supported by primary and secondary data was employed in this research. Primary data were collected through direct interviews in the study area, including information regarding farmer profiles, land area, farming income and feasibility, as well as farmer motivation in cocoa cultivation. Secondary data were sourced from literature such as books, journals, and agencies or institutions relevant to the research topic. The analysis results comparing 5 farmer groups in Putat Village indicate that the highest farming income was achieved by the Sidodadi farmer group, amounting to IDR 21,838,000.00, whereas the lowest income belonged to the Pamor farmer group at IDR 6,899,000.00. All 5 farmer groups were deemed feasible for conducting cocoa farming operations, with the lowest feasibility score recorded by the Ngudi Raharjo farmer group, which had an R/C ratio of 2.6 and a B/C ratio of 1.6. The income level significantly affected the motivation of the cocoa farmer respondents. Furthermore, issues regarding pests and diseases, along with the existence of farmer groups, also influenced farmers' motivation to increase cocoa productivity.